Pengaruh Kepercayaan Merk Global Dan Kualitas Produk Terhadap Keputusan Pembelian Mobil Toyota Avanza Di PT. Astra Internasional, Tbk Toyota Auto 2000 Karawang Periode 2023 - Adhy Fatkhuyani; M. Agus Cholik (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This research aims to examine the influence of global brand trust and product quality on consumerpurchasing decisions for Toyota Avanza vehicles at PT Astra International, Tbk – Toyota Auto 2000Karawang during the 2023 period. The study is motivated by the enduring dominance of the ToyotaAvanza as a family car in Indonesia, amid intensifying competition in the automotive industry andshifting consumer preferences. The research applies a quantitative approach, utilizing a survey methodwith structured questionnaires distributed to 100 respondents who are customers of Toyota Auto 2000Karawang. The independent variables under study are global brand trust and product quality, while thedependent variable is purchasing decision. Data were analyzed using validity and reliability tests,classical assumption tests, multiple linear regression analysis, as well as t-tests and F-tests. Thefindings reveal that: (1) global brand trust has a positive and significant effect on purchasing decisions;(2) product quality has a positive and significant effect on purchasing decisions; and (3) global brandtrust and product quality simultaneously exert a significant influence on purchasing decisions for ToyotaAvanza vehicles. These results underscore that consumers’ decisions are shaped not only by functionalproduct attributes but also by brand image and trust in a global brand. From an academic standpoint,this study enriches consumer behavior literature in the automotive sector. From a practical perspective,the results provide valuable insights for PT Astra International, Tbk – Toyota Auto 2000 Karawang informulating marketing strategies, enhancing service quality, and maintaining brand reputation tostrengthen consumer purchasing decisions.Keywords: Global Brand Trust, Product Quality, Purchase Decision, Toyota Avanza, Auto 2000Karawang